A higher ctDNA fraction decreases survival in regorafenib‐treated metastatic colorectal cancer patients. Results from the regorafenib's liquid biopsy translational biomarker phase II pilot study. Issue 6 (16th October 2020) - Unseld, Matthias; Belic, Jelena; Pierer, Kerstin; Zhou, Qing; Moser, Tina; Bauer, Raimund; Piringer, Gudrun; Gerger, Armin; Siebenhüner, Alexander; Speicher, Michael; Heitzer, Ellen; Prager, Gerald W.
Abstract: The predictive effect of circulating tumor DNA (ctDNA) in colorectal cancer (CRC) treatment is still highly discussed. The primary objective of our study was to investigate a possible prognostic/predictive value of ctDNA under regorafenib treatment. This prospective multicenter translational biomarker phase II pilot study enrolled 30 metastatic CRC patients (67% men, 33% women) treated with regorafenib. ctDNA was assessed in plasma before treatment start and at defined time points during administration. Measurement of tumor fraction as well as mutation and copy number analysis of CRC driver genes were performed by next‐generation sequencing approaches. Multivariate analyses for survival and treatment efficacy were adjusted to age, gender and Eastern Cooperative Oncology Group. Disease control rate was 30%. Median tumor fraction at baseline was 18.5% (0‐49.9). Mutations in CRC driver genes or genes involved in angiogenesis were identified in 25 patients (83.3%). KRAS mutations were detected in 13 of 14 KRAS ‐positive tumors; in three patients without KRAS mutation in the respective tumors, acquired mutations as a consequence of prior anti‐EGFR treatment were detected. In a subset of patients, novel occurring mutations or focal amplifications were detected. A tumor fraction of 5% and higher at baseline was significantly associated with a decreased OS ( P = .022; hazard ratio 3.110 (95% confidence interval: 1.2‐8.2). ctDNA is detectable in a high proportion of mCRC patients. Higher ctDNA levels are associated with survival among regorafenib treatment. Moreover, our data highlight the benefit of a combined evaluation of mutations and somatic copy number alterations in advanced cancer patients. What's new?: The predictive effect of circulating tumor DNA (ctDNA) in colorectal cancer (CRC) treatment remains under discussion. This prospective multicenter translational biomarker phase II pilot study investigated the possible predictive/prognostic value of ctDNA in metastatic CRC patients treated with regorafenib, a multi‐kinase inhibitor. Overall, alterations in CRC driver genes could be identified in 87% of patients. The data indicated that a tumor fraction of >5% was significantly associated with decreased survival. Moreover, the combined evaluation of mutations and somatic copy number alterations enabled the detection of novel changes occurring during treatment.